Water-soluble lectin (WSMoL) from Moringa oleifera seeds treatment recovers glycemic levels and improves left ventricular ejection fraction on Type-2 Diabetes mice model - VERA-NUÑEZ,NARENDRA (2021)
Abstract Moringa oleifera, a plant widely used in traditional medicine as well as for water purification, contains a lectin on its seeds named WSMoL which modulates several immune characteristics and has shown cardiac safe properties. Here, we tested the hypothesis that WSMoL is able to recover fasting glucose levels and to improve the cardiac left ventricular (LV) function in a type 2 diabetes mellitus (T2DM) mice model. T2DM was induced in adult C57BL/6 mice by combining a high fat diet and low doses of Streptozotocin. Mice were randomly divided in two groups: i. received WSMoL for 21 consecutive days by gavage (T2DM + WSMoL) and ii. received saline solution (T2DM). Metabolic parameters and LV function were assessed. WSMoL was able to reduce fasting blood glucose levels in T2DM mice after 2 weeks of treatment, when compared to T2DM untreated group. Regarding to cardiac LV function, the T2DM + WSMoL group depicted ejection fraction values comparable to non-diabetic group. Our results show: i. WSMoL treatment presented a potent hypoglycemic effect decreasing insulin resistance and ii. WSMoL was able to improve cardiac LV ejection fraction. Collectively, the results presented here show WSMoL as a potential hypoglycemic agent to be tested in T2DM patients.